Eyelid Coloboma in a Newborn with VACTERL Association - Timilsina, Mukunda; Gauchan, Eva; Koirala, Deepak Prasad (Journal of Nepal Paediatric Society, 2018)
VACTERL is used to denote vertebral abnormalities (V), anal atresia (A), cardiac defects (C), tracheo-esophageal fistula (TE), renal or radial abnormalities (R), and limb abnormalities (L). This is a case report of a neonate delivered to Manipal Teaching Hospital, Pokhara with features suggestive of VACTERL association.